First record of ashy minivet Pericrocotus divaricatus in Kathmandu Valley, Nepal - Gosai, Kiran; Gosai, Kamal Raj; Dhakal, Anju Kumari; Shrestha, Suman Man (Nepalese Journal of Zoology, 2023)
The status and distribution of birds in Nepal is being updated as the number of bird species and records increase. We present a distributional update of ashy minivet Pericrocotus divaricatus, a rare winter visitor to Nepal. We made an opportunistic sighting of the species on 25 February 2022 during a bird survey along the Hanumante River, Bhaktapur, Nepal. AM had been previously recorded in Nepal at Koshi Tappu Wildlife Reserve and at Sauraha, Chitwan District, but not in the Kathmandu Valley. Thus, our record of this species in Bhaktapur (Kathmandu Valley) is a new distributional record of the species in Nepal. Rapid change in land use is posing threats to bird habitats; therefore, we recommend maintaining a continuous green corridor along the Hanumante River.